Comparison of PGE2 gel alone versus sequential use of Foley’s catheter and PGE2 gel in the ripening of unfavorable cervix: a retrospective study - Shankarappa, Veena Kadadanamari; Natarajan, Preethi; Natarajan, Monisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labor is common procedure practiced in obstetrics. Various methods used for cervical ripening are lacking the proven superiority of one over other. Our study aimed at comparing intracervical PGE2 gel used alone with sequential use of Foley’s catheter and PGE2 gel in order to appreciate reduction in LSCS rate without affecting neonatal outcome. Methods: The retrospective study was conducted among cases delivered with labor induction between June 2017 to January 2019. Among 104 pregnant women, group1 had received PGE2 gel alone and group 2 had received Foley’s followed by PGE2 gel for induction. The primary outcome included Cesarean section rate and secondary outcomes included improvement in Bishop scores, induction to delivery interval, indication for LSCS, APGAR scores, NICU admission. Data was analyzed and compared. Results: Both groups were comparable with respect to maternal age, gestational age and indication for induction. There was no significant difference in the mean pre-induction Bishop score between groups. Mean IDI was higher in group 2. There was no difference in mode of delivery, neonatal and maternal morbidity between groups. Higher number of women went into spontaneous labor among group 2 and higher number of women needed oxytocin among group 1 for augmentation. Conclusions: Intra cervical PGE2 can be safely used among women with unfavorable cervix to achieve faster delivery without increasing LSCS rate. Whereas sequential use of Foley’s catheter and PGE2 gel can be safer alternative for induction of delivery with low risk of oxytocin augmentation when quicker delivery is not needed.